Pobreza, descentralizacion y bosques en el norte amazonico boliviano - Fuentes, D.; Haches, R.; Maldonado, R.; Albornoz, M.A.; Cronkleton, P.; Jong, W. de; Becker, M. (Center for International Forestry Research, 2005)
This Spanish language book provides an overview of Bolivia’s Amazonian department of Pando, its geography and the conditions faced by rural residents and local government. The book’s six chapters provide detailed analysis of regional poverty and the government agencies and civil society actors responsible for poverty alleviation. Key topics include how Bolivia conceptualizes poverty, how data on poverty in the country are collected and reported, and how this information results in specific poverty reduction activities. The first three chapters provide a comprehensive overview of Bolivia's policies and legislation related to poverty reduction. Central to these are the Poverty Reduction Strategy and the National Dialogue Law that define the mechanisms that guide actions at the local level. The first three chapters form the introduction to a detailed analysis of poverty in the Amazon region of northern Bolivia, a region that relies largely on forestry production, and where CIFOR has been conducting social research since the mid 1990s. The book provides an excellent introduction to readers interested in poverty at the forest margins in Bolivia.